ANALISIS KESALAHAN SISWA SMA KELAS X DALAM MENYELESAIKAN SOAL KONEKSI MATEMATIS MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Muhammad Ikhsan Nuralam; Eka Senjayawati (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
One of the mathematics topics covered in class X SMA is the Three Variable Linear Equation System (SPLTV). Students frequently make mistakes when attempting to solve SPLTV-related problems. This research aims to examine the errors made by class X SMA students when attempting to solve mathematical connection problems in SPLTV content. The type of research is qualitative descriptive. There were 36 class X students of SMAN 1 Batujajar as participant in this study, 11 male and 25 female. This study collected data using a five-question of the SPLTV mathematical connection test. The collected data is then examined, the data processed and presented, and conclusions are drawn from the processed data. As indicated by the discoveries of this review, students' errors in solving mathematical connection problems involving SPLTV material contain a very high criteria for indicators of seeking connections or other procedures in equivalent representations and a high criteria for indicators that make use of connections between mathematical topics and other topics.